The Application of Ethanolic Ultrasonication to Ameliorate the Triterpenoid Content Extracted from Vietnamese Ganoderma lucidum with the Examination by Gas Chromatography. Issue 10 (9th March 2021) - Dat, Tran Do; Viet, Nguyen Duc; My, Phan Le Thao; Linh, Nguyen Thi; Thanh, Vuong Hoai; Linh, Nguyen Thi Thuy; Ngan, Nguyen Thi Kim; Linh, Ngo Thi Thuy; Nam, Hoang Minh; Phong, Mai Thanh; Hieu, Nguyen Huu
Abstract: In this study, to investigate the extraction of triterpenoids from the Vietnamese red G. lucidum by ultrasound‐assisted extraction (UAE) method using ethanol as a solvent, the determination of the four single factors influence on the triterpenoid content including liquid‐to‐solid ratio, extraction power, extraction temperature, and extraction time was carried out for the performance of experiments on simultaneous effects by Central Composite design. The results showed that based on ultraviolet‐visible spectroscopy analysis, the highest yield of triterpenoids could be achieved with value of 18.3751 mg/g under optimal extraction conditions including extraction time of 60 min, ultrasonic power of 360 W, liquid‐to‐solid ratio of 38 : 1 mL/g, and ultrasonic temperature of 48 °C. To determine the characteristics of the obtained extract, the Gas chromatography‐mass spectrometry, the Fourier‐transform infrared spectroscopy, scanning electron microscope, and the thermogravimetric analyzer were employed in this study. Besides, for antioxidant capacity evaluation, the DPPH free radical scavenging assay, H2 O2 scavenging assay, and the ABTS radical cation decolorization assay were carried out whereas the anticancer evaluation results denoted the potential for anticancer agents of G. lucidum extract. Therefore, it could be concluded that UAE is a promising method for triterpenoid extraction with antioxidant properties. Abstract : This research demonstrates the procedure of using ultrasonication assisted extraction method for triterpenoid extraction from Vietnamese G. lucidum . Different significant extraction factors such as liquid‐to‐solid ratio, ultrasonic power, extraction temperature, and extraction time on triterpenoid content were investigated to optimize the extraction process. In addition, the extracts under optimal conditions were used to determine antioxidant, antibacterial, and anticancer properties for application in multifarious areas such as functional food and cosmetics.